Confrontation versus withdrawal: Cultural differences in responses to threats to honor. (May 2013) - Cross, Susan E.; Uskul, Ayse K.; Gerçek-Swing, Berna; Alözkan, Cansu; Ataca, Bilge
This study compares evaluations by members of an honor culture (Turkey) and a dignity culture (northern USA) of honor threat scenarios, in which a target was the victim of either a rude affront or a false accusation, and the target chose to withdraw or confront the attacker. Turkish participants were more likely than American participants to evaluate positively the person who withdrew from the rude affront and the person who confronted the false accusation. Participants in both societies perceived that others in their society would endorse confrontation more than withdrawal in both types of scenarios, but this effect was larger for Turkish than American participants. Honor values were associated with evaluations of the targets most strongly among Turkish participants who read about a person who confronted their attacker. These findings provide insight into the role of cultural norms and individual differences in the ways honor influences behavior.